(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
The legacy of Jansenism in the reflection of Francesco Ruffini and Arturo Carlo Jemolo: some first reconstructive ideas ABSTRACT: This contribution intends to delve deeper into the choice that two famous Italian ecclesiasticists, Ruffini and Jemolo, made during the second decade of the twentieth century to study a topic that was not purely juridical, namely the Jansenist movement. After an overview of the writings of the two masters on the subject, in light of the historical and cultural context of the time, adequate space is dedicated to an investigation into the origins of these contributions and their related implications. Thus, on the one hand, we come to better understand the meaning of the choice made and, on the other, to reflect on the relevant methodological profiles that characterized the works examined, opening up interesting and paradigmatic prospects for the future. SOMMARIO: 1. Premessa - 2. Il Giansenismo brevi cenni di inquadramento - 3. Il contesto: i prodromi del Diritto Ecclesiastico - 3.1. Alcune spigolature di Francesco Ruffini su Manzoni, Cavour e il giansenismo - 3.2. Il problema del giansenismo in Arturo Carlo Jemolo: spunti di riflessione - 4. Una “valutazione comparativa” - 5. Considerazioni conclusive.